Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1161/01.hyp.35.2.587
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure–Independent Effects in Rats With Human Renin and Angiotensinogen Genes

Abstract: Abstract-The blood pressure-independent effects of angiotensin II (Ang II) were examined in double transgenic rats (dTGR) harboring human renin and human angiotensinogen genes, in which the end-organ damage is due to the human components of the renin angiotensin system. Triple-drug therapy (hydralazine 80 mg/L, reserpine 5 mg/L, and hydrochlorothiazide 25 mg/L in drinking water) was started immediately after weaning. Triple-drug therapy normalized blood pressure and coronary resistance, only partially prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
106
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 45 publications
6
106
1
2
Order By: Relevance
“…The activated RAAS in these animals leads to severe hypertension with renal damage, including albuminuria, elevated serum creatinine, renal infiltration of macrophages, and ECM deposition. 68,70 In this model, aliskiren (0.3 or 3 mg kg -1 per day) normalized the BP and reversed existing renal damage, evidenced by normalizing albuminuria and serum creatinine levels. Furthermore, glomerular collagen IV accumulation and renal macrophage and lymphocyte contents were lowered.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 84%
See 1 more Smart Citation
“…The activated RAAS in these animals leads to severe hypertension with renal damage, including albuminuria, elevated serum creatinine, renal infiltration of macrophages, and ECM deposition. 68,70 In this model, aliskiren (0.3 or 3 mg kg -1 per day) normalized the BP and reversed existing renal damage, evidenced by normalizing albuminuria and serum creatinine levels. Furthermore, glomerular collagen IV accumulation and renal macrophage and lymphocyte contents were lowered.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 84%
“…These studies showed the efficacy of aliskiren in high Ang II-induced renal injury and suggested a beneficial effect of the drug in complement-dependent renal disease. Notably, an earlier study of dTGR showed that when the renin inhibitor remikiren and a non-RAAS blocking anti-hypertensive therapy were compared at comparable BP-lowering doses, remikiren showed stronger renoprotection, 70 suggesting BP-independent effects of renin inhibition.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 99%
“…Angiotensinconverting enzyme inhibitors, alone or in combination with AT 1 R blockers, have been shown to decrease urine protein excretion, even in normotensive subjects and independent of blood pressure. 2,30 In diabetic subjects whose aldosterone levels increased during angiotensin-converting enzyme inhibition, the addition of an aldosterone blocker decreased urinary protein even further, without any changes in blood pressure. 31 In our studies, the decrease in urinary protein excretion by AT 1 R AS-ODN occurred in WKY and SHR, but the decrease in protein excretion was greater in SHR such that it was no longer different from that seen in AS-ODN-treated WKY.…”
Section: Discussionmentioning
confidence: 99%
“…G enetic manipulations that increase the activity of the renin-angiotensin system (RAS) systemically [1][2][3][4][5] or in specific organs (eg, brain and kidney) elevate blood pressure. 6,7 For example, overexpression of angiotensinogen and renin in renal proximal tubules 6 or in neurons and glia cells in brain 7 increased blood pressure without increasing circulating renin levels.…”
mentioning
confidence: 99%
“…Ang II concentrations in the circulation and in tissues are about fivefold higher in dTGR compared to non-transgenic SD controls. 27,33 We have previously shown that myocardial, renal, and vascular damage in dTGR are age-dependent. In fact, immediately after weaning at age 3 to 4 weeks, myocardial and renal tissue morphology by light microscopy are indistinguishable between dTGR and normotensive SD rats.…”
Section: Discussionmentioning
confidence: 99%